The ‘triradiate bump’: a novel radiographic sign that may confound assessment of acetabular retroversion - Morris, William Z. (J Child Orthop, 2016)
PURPOSE: The triradiate cartilage transiently projects medially within the pelvic brim around the time of triradiate closure, mimicking the ischial spine sign. The purpose of this study was to characterize this newly identified radiographic sign using a longitudinal radiographic study. METHODS: We identified 72 subjects from a longitudinal radiographic study of healthy adolescents, each with at least four consecutive, annual anterior−posterior radiographs of the left hip, including physeal closure. Images were reviewed to identify the presence of the triradiate bump, the year it was most prominent, and the number of years relative to triradiate closure after which it had completely remodeled. RESULTS: The transient medial projection of the triradiate cartilage (triradiate bump) was identified in 26/40 (65 %) females and 22/32 (69 %) males (p = 0.74). The medial projection of the triradiate cartilage was most prominent at 10.8 ± 0.8 years of age in females and 12.6 ± 0.7 years of age in males (p < 0.001). The triradiate cartilage projected medially a mean of 4.7 ± 0.8 or 5.1 ± 1.4 mm for females and males, respectively (p = 0.29), but remodeled completely in all cases around triradiate closure. CONCLUSIONS: The transient medial projection of the triradiate cartilage within the pelvic brim, the ‘triradiate bump sign’, is a common radiographic finding in healthy adolescents around the time of closure of the triradiate cartilage that may mimic the ischial spine sign. These two signs can be distinguished as the projection of the ischial spine is located more inferiorly within the pelvic brim and the triradiate bump has a horizontal limb of radiolucency extending to its medial border.